Microstructure and Magnetic Properties of Cobalt and Zinc Containing Magnesium Alloys. (2016) - Demminger, Christian; Klose, Christian; Maier, Hans Jürgen
Abstract: The magnetic properties of lightweight alloys based on magnesium and cobalt offer a novel way to measure mechanical loads throughout the entire structural component using the magnetoelastic effect. Since the solubility of cobalt in the magnesium matrix is negligible, the magnetic properties mainly originate from Co-rich precipitates. Size and distribution of the Co-containing phases within the alloy's microstructure can be influenced during the initial processing method of the alloy. Specifically, the cooling rate in the casting processes has a major influence on the resulting magnetic properties. In this study, Mg-Co-based alloys were produced by several casting methods which feature substantially different cooling rates, i.e. gravity sand casting, gravity die casting and high-pressure die casting. The differences between the manufactured alloys' micro- and phase structures are compared and the superior magnetic and mechanical properties of the high-pressure die cast material are demonstrated.